Determining Cut-Off Points for the Dental Fear Survey - Maurício Antônio Oliveira; Cristiane Baccin Bendo; Saul Martins Paiva; Miriam Pimenta Vale; Júnia Maria Serra-Negra (The Scientific World Journal)
Objective. To determine a high fear cut-off point score for the Dental Fear Survey (DFS) using a single-item self-report questionnaire. Methods. The DFS, a 20-item questionnaire assessing fear of dental treatment, was completed by 1,256 participants with a mean age of 22.3 years (SD = 5.1). Another self-report questionnaire was used to collect data on previous dental experiences. A high fear cut-off point score was determined by calculating the receiver operating characteristic (ROC) curve for the DFS. Descriptive statistics and multinomial logistic regression were calculated; a significance level of p<0.05 was used for all tests. Results. The ROC curve indicated that a DFS score ≥53 corresponds to a sensitivity of 88.9% and a specificity of 92.5%. Most participants (n=895; 71.5%) reported no fear of going to the dentist. There was significant association between DFS score and fear assessed with the question “Are you fearful of going to the dentist?” (p<0.001). Conclusion. A cut-off point of 53 on the DFS total score represents the best compromise between sensitivity and specificity and can be used to predict high dental fear.